2012
DOI: 10.9734/ajea/2012/1128
|View full text |Cite
|
Sign up to set email alerts
|

Entomofauna of Oil Palm Tree Inflorescences at La Mé Experimental Station (Côte d’Ivoire)

Abstract: Pollination of oil palm tree is mainly entomophilous. The inflorescences of this plant lodge many insects. The identification and quantification of these insects have proven ability to hold their pollination. The entomofauna of female and male inflorescences was inventoried and quantified at La Mé, a station of CNRA, the National Center of Agronomic Research of Côte d'Ivoire (West Africa) for a period of 2 years. The insects of the male inflorescences were listed at the beginning, the full and the end of anthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
2
1
0
2
Order By: Relevance
“…Elaeidobius kamerunicus was more abundant on male inflorescences than female inflorescences, and this is similar to the results of Hala et al (2012). Our examinations were more detailed than those of Tuo et al (2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Elaeidobius kamerunicus was more abundant on male inflorescences than female inflorescences, and this is similar to the results of Hala et al (2012). Our examinations were more detailed than those of Tuo et al (2011).…”
Section: Discussionsupporting
confidence: 89%
“…We demonstrated that adult weevils were most abundant on the female flowers on the 2nd day of anthesis. This finding is similar to that of Hala et al (2012) but differs from the results of Syed (1979Syed ( , 1982, who reported that the adult weevil population increased to a maximum on the female inflorescences during the 2nd and 3rd days of anthesis. The differences between our observations and those reported by Syed (1979Syed ( , 1982 could perhaps be due to differences in climate and location.…”
Section: Discussionsupporting
confidence: 67%
“…Visitation of weevils increases due to opened flowers during the anthesis period (Yue et al, 2015). Visitations of weevils are high on the first day of anthesis of female inflorescence, but this observation is differed from Hala et al (2012) and Yue et al (2015). They reported that the visitations of weevils are higher on the second and third days of anthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Cette identification a été faite à l'aide d'une loupe binoculaire en se servant de la collection des insectes des inflorescences du palmier à huile disponible sur cette station. Les travaux antérieurs ont également été consultés pour cette identification (Hala et al, 2012).…”
Section: Identification Des Espèces D'insectesunclassified
“…L'absence de certains de ces insectes pollinisateurs ou la diminution de leurs populations dans les palmeraies entraîne systématiquement une diminution du taux de fruits fécondés (Syed et al, 1982 ;Mariau et Genty, 1988;Mariau et al, 1991 (Syed, 1979 ;Desmier de Chenon, 1981, Mariau et Genty, 1988Mariau et al, 1991). L'espèce E. kamerunicus transporte plus de grains de pollen et s'est montré plus efficace dans la pollinisation (Kouakou et al, 2014) Les travaux récents sur l'entomofaune des inflorescences du palmier à huile en Côte d'Ivoire ont révélé des fluctuations spatio-temporelles importantes et une diminution de la densité de ces principaux pollinisateurs (Hala et al, 2012 ;Koua et al, 2013). L'influence de ces fluctuations sur le taux de nouaison n'a pas été clairement établie.…”
Section: Introductionunclassified